2017
DOI: 10.1590/0103-8478cr20160098
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative rescue and ex vitro system production of Tibouchina sellowiana clonal plants by cutting and mini-cutting

Abstract: We aimed to evaluate the rooting potential of Tibouchina sellowiana through the experiments: I - Cuttings from current-year shoots and epicormic shoots were submitted to IBA concentrations: 0, 500, 1000, 1500 and 2000mg L-1, in a factorial arrangement 2 x 5 (two types of cuttings x five IBA concentrations), with four replicates and 20 cuttings each; II - mini-stumps of Tibouchina sellowiana were submitted to successive shoots collecting during the four seasons, in a split-plot design, with five replications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…However, its exogenous application has been questioned in previous studies of the mini-cutting technique of native species, using juvenile propagules, where the rooting of mini-cuttings with IBA is not favoured, and might actually be harmful to the induction of root beginnings, as for P. peroba. This tendency has been corroborated for Cedrela fissilis (Xavier et al, 2003), Anadenanthera macrocarpa (Dias et al, 2012), Araucaria angustifolia (Pires et al, 2013)este trabalho objetivou avaliar a influência de concentrações de ácido indolbutírico (AIB, Tibouchina sellowiana (Fragoso et al, 2017), Peltophorum dubium (Mantovani et al, 2017), and Plathymenia reticulata (Pessanha et al, 2018). The application of high concentrations of synthetic auxin may lead to toxicity owing to hormonal imbalance (Rinaldi et al, 2018).…”
Section: Substrates and Iba In Rhizogenesis Of Paratecoma Perobamentioning
confidence: 89%
See 1 more Smart Citation
“…However, its exogenous application has been questioned in previous studies of the mini-cutting technique of native species, using juvenile propagules, where the rooting of mini-cuttings with IBA is not favoured, and might actually be harmful to the induction of root beginnings, as for P. peroba. This tendency has been corroborated for Cedrela fissilis (Xavier et al, 2003), Anadenanthera macrocarpa (Dias et al, 2012), Araucaria angustifolia (Pires et al, 2013)este trabalho objetivou avaliar a influência de concentrações de ácido indolbutírico (AIB, Tibouchina sellowiana (Fragoso et al, 2017), Peltophorum dubium (Mantovani et al, 2017), and Plathymenia reticulata (Pessanha et al, 2018). The application of high concentrations of synthetic auxin may lead to toxicity owing to hormonal imbalance (Rinaldi et al, 2018).…”
Section: Substrates and Iba In Rhizogenesis Of Paratecoma Perobamentioning
confidence: 89%
“…(Pessanha et al, 2018), Tibouchina selowiana (Cham.) Cogn (Fragoso et al, 2017), Peltophorum dubium (Spreng.) Taub (Mantovani et al, 2017), and Cabralea canjerana (Vell.)…”
Section: Introductionmentioning
confidence: 99%
“…Concerning mini-cuttings, previous studies have demonstrated that IBA application does not favor adventitious rooting; as the example of Eucalyptus grandis x E. globulus clones (Borges et al, 2011), Anadenanthera macrocarpa (Dias et al, 2012), Araucaria angustifolia (Pires et al, 2013), Tectona grandis (Badilla et al, 2016), Tibouchina sellowiana (Fragoso et al, 2017), Peltophorum dubium (Mantovani et al, 2017), Plathymenia reticulata (Pessanha et al, 2018) and Paratecoma peroba (Araújo et al, 2019). These studies corroborate with the results obtained for Mimosa caesalpiniifolia.…”
Section: Iba Infl Uencementioning
confidence: 99%
“…Cogn), a species of ornamental importance, has low seed germination rates and a high degree of plant unevenness. Thus, rooting of lignified seedlings is complex, being preferable the use of mini-cuttings for presenting less lignification and greater endogenous hormonal balance, favorable to the emission of roots, which makes the technique viable for the production of seedlings of this species (Fragoso et al, 2017). As with other species, it is important to emphasize that satisfactory control of climatic conditions in the production environment is an essential factor for rooting success.…”
Section: Mini-cutting In the Production Of Forest Species Seedlingsmentioning
confidence: 99%